Organic Aerosol Processing During Winter Severe Haze Episodes in Beijing. Issue 17 (2nd September 2019) - Zhao, Jian; Qiu, Yanmei; Zhou, Wei; Xu, Weiqi; Wang, Junfeng; Zhang, Yingjie; Li, Linjie; Xie, Conghui; Wang, Qingqing; Du, Wei; Worsnop, Douglas R.; Canagaratna, Manjula R.; et al.
Abstract: Organic aerosol (OA) constituted a large fraction of aerosol particles during severe haze episodes in winter in northern China, yet our understanding of its physical and chemical processing was limited. Here we investigate the sources and processes of OA during four haze episodes in winter in 2016 using high‐resolution aerosol mass spectrometer. The PM2.5 reached 400 μg/m 3 during the severest episode (Ep1) when Beijing issued a red alert and implemented strict emission controls. Our results showed that secondary OA (SOA) dominated OA during haze episodes on average accounting for 46–66% of OA and was comparable to secondary inorganic aerosol (SIA) with the SOA/SIA ratios being 0.51–0.72. Primary OA from fossil‐fuel combustion, biomass burning, and cooking presented very strong diurnal variations during haze episodes and contributed up to 60% in OA at night. Comparatively, the changes in semivolatile and low‐volatility SOA were relatively small except a substantial increase in aqueous phase‐related oxidized OA (aq‐OOA) during Ep1 with high relative humidity and aerosol water content. aq‐OOA fell well into a small region in the middle of the triangle plot of f 44 versus f 43 (fraction of m/z 44 and 43 in OA, respectively), which can be used as a diagnostic for the presence of aqueous phase processing of SOA. In addition, the increases of SO2 + /SO3 + as a function of relative humidity, the triangle plot of f H 2 SO 4 + versus f H SO 3 +, and high nitrogen‐to‐carbon ratio in aq‐OOA suggest the potential formation of sulfur‐ and nitrogen‐containing organic compounds through aqueous phase processing. Key Points: Secondary organic aerosol (46–66%) dominates organic aerosol during winter haze episodes in urban Beijing Aqueous phase‐related OA fell well into a unique region in the triangle plot of f 44 versus f 43 Evidence showed potential formation of N‐ and S‐containing organic compounds through aqueous phase processing